Examining the Handling of Stunting in The Osing Tribe as An Effort to Banyuwangi Zero Stunting - Putri, Nofia Erika Putri; Putri, Novita Surya; Permata, Dinda Ayu; Prasetyo, Lintang; Lestari, Hestin Ayu; Rahmadani, Muhammad Naufal (International Journal of Nursing and Health Services (IJNHS), 2024)
Background: Handling stunting in the Gitik Community Health Center working area can reduce stunting rates significantly. Objective: This research aims to examine the handling of stunting in the Osing tribe as an effort to create zero stunting in Banyuwangi. Method: The research design uses qualitative with a phenomenological approach. By using a purposive sampling technique, 9 participants were obtained, namely mothers who had stunted-free children and mothers who had stunted children. Data collection was carried out using semi-structured interviews. Data analysis used the Colaizzi method with the help of Nvivo 12 software. Result: 5 themes and 13 subthemes were analyzed for the main participants in this research; 1) Grieving; 2) Information; 3) Individual Motivation; 4) Social motivation; 5) Behavioral skills. Conclusion : Handling stunting among the Osing tribe in the Gitik Health Behavior (IMB) theory. Handling stunting by providing information Center Working Area is by the Information Motivation Skills with health education to mothers, so that mothers have personal motivation, supported by social motivation in handling stunting and maternal behavioral skills in caring for and providing parenting to children